Solid Oxide Cell Electrode Nanocomposites Fabricated by Inkjet Printing Infiltration of Ceria Scaffolds - Simone Anelli; Luis Moreno-Sanabria; Federico Baiutti; Marc Torrell; Albert Tarancón (Nanomaterials, 2021)
The enhancement of solid oxide cell (SOC) oxygen electrode performance through the generation of nanocomposite electrodes via infiltration using wet-chemistry processes has been widely studied in recent years. An efficient oxygen electrode consists of a porous backbone and an active catalyst, which should provide ionic conductivity, high catalytic activity and electronic conductivity. Inkjet printing is a versatile additive manufacturing technique, which can be used for reliable and homogeneous functionalization of SOC electrodes via infiltration for either small- or large-area devices. In this study, we implemented the utilization of an inkjet printer for the automatic functionalization of different gadolinium-doped ceria scaffolds, via infiltration with ethanol:water-based La1−xSrxCo1−yFeyO3−δ (LSCF) ink. Scaffolds based on commercial and mesoporous Gd-doped ceria (CGO) powders were used to demonstrate the versatility of inkjet printing as an infiltration technique. Using yttrium-stabilized zirconia (YSZ) commercial electrolytes, symmetrical LSCF/LSCF–CGO/YSZ/LSCF–CGO/LSCF cells were fabricated via infiltration and characterized by SEM-EDX, XRD and EIS. Microstructural analysis demonstrated the feasibility and reproducibility of the process. Electrochemical characterization lead to an ASR value of ≈1.2 Ω cm2 at 750 °C, in the case of nanosized rare earth-doped ceria scaffolds, with the electrode contributing ≈0.18 Ω cm2. These results demonstrate the feasibility of inkjet printing as an infiltration technique for SOC fabrication.